1997
DOI: 10.1038/nm1097-1117
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vpr suppresses immune activation and apoptosis through regulation of nuclear factor κB

Abstract: The HIV-1 accessory gene product Vpr can influence viral pathogenesis by affecting viral replication as well as host cell transcription and proliferation. We have investigated the effects of Vpr on host cell activation and confirm that it influences cellular proliferation. However, we have also found that Vpr modulates T-cell receptor (TCR)-triggered apoptosis in a manner similar to that of glucocorticoids. In the absence of TCR-mediated activation, Vpr induces apoptosis whereas in its presence, Vpr interrupts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
175
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(183 citation statements)
references
References 40 publications
6
175
2
Order By: Relevance
“…An early report suggested that the interaction of Vpr and GR was necessary for apoptosis to be initiated. 17 Studies also suggested that Vpr directly targets the mitochondria for membrane potential depolarization, suggesting that Vpr-ANT interaction is required. 37 Chen and colleagues, via RNAi-mediated loss of function experiments, concluded that the depletion of Wee1 is also required for Vpr to prompt apoptosis.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
See 2 more Smart Citations
“…An early report suggested that the interaction of Vpr and GR was necessary for apoptosis to be initiated. 17 Studies also suggested that Vpr directly targets the mitochondria for membrane potential depolarization, suggesting that Vpr-ANT interaction is required. 37 Chen and colleagues, via RNAi-mediated loss of function experiments, concluded that the depletion of Wee1 is also required for Vpr to prompt apoptosis.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…Lastly, it is clear that Vpr can directly target the mitochondria for depolarization, but whether this in itself is sufficient for driving apoptosis in vivo remains undetermined. For instance, Vpr's signaling through the GR pathway has been shown to inhibit the survival NF-kB pathway, 17 which can ideally repress antiapoptotic factors such as Bcl-2. Therefore, the elucidated factors and the pathways discussed may not be mutually exclusive.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vpr can induce apoptosis through a variety of mechanisms (Jacotot et al, 2000;Patel et al, 2000;Stewart et al, 2000). In one study, suppression of nuclear factor-kB (NF-kB) activity through the induction of IkB was linked to Vprmediated apoptosis (Ayyavoo et al, 1997). In other studies, induction of apoptosis by Vpr was attributed to rapid dissipation of the mitochondrial transmembrane potential, association of Vpr with the adenine nucleotide translocator, release of cytochrome c and activation of caspase-3 (Jacotot et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Since a major mechanism for CD4+ T cell depletion in HIV-infected patients is apoptosis, which is induced by HIV through multiple pathways in both infected cells and noninfected "bystander" cells [39], it is expected that the apoptotic effect of Vpr may contribute to CD4+ T cell depletion. Although it is well accepted that Vpr induces apoptosis, there are studies suggesting that Vpr may also act as a negative regulator of T cell apoptosis [40,41]. In addition, it is debated whether Vpr-induced apoptosis is a result of G2 arrest.…”
Section: Viral Protein R (Vpr)mentioning
confidence: 99%